Penyuluhan Stunting di Desa Kadipaten Wonosobo Melalui KKN Mandiri Berbasis Hukum Keluarga Islam - Muntako, Muntako; Hendrawan, Hendrawan; Widodo, Yuda; Yuliana, Yuliana; Dewanto, I Joko; Muhiran, Muhiran; Afiat, M (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
The prevention of stunting in Indonesia, particularly in Desa Kadipaten, Kabupaten Wonosobo, is a key focus in efforts to improve the quality of life in the community. Stunting, which affects the physical and mental development of children, can be minimized through various approaches, one of which is legal awareness emphasizing parental responsibility for child health. As part of the Kuliah Kerja Nyata (KKN) Mandiri program, students from the Law Department, Class C1, Universitas Tangerang, implemented a community service program in Desa Kadipaten to enhance the community’s understanding of stunting prevention through an Islamic family law approach. From the perspective of Islamic family law, parents have an obligation to provide adequate nutrition and ensure the health of their children, a responsibility that must be fulfilled to guarantee the optimal realization of children’s rights. This program was carried out through socialization, training for housewives, and discussions with community leaders and the village head. The results of this activity show an increase in community awareness regarding the importance of a healthy lifestyle and proper nutrition management in preventing stunting. The legal awareness provided through this approach is expected to strengthen parental commitment in fulfilling children’s rights and support the development of a healthy and quality generation.